Andrej Belyjs Rezeption der Philosophie Kants, Nietzsches und der Neukantianer - Andrea, Zink (Slavistische Beitraege, 1998)
Andrej Belyj's novel "Peterburg" introduces to the reader a positivistic father, a neo-Kantian son and a revolutionary with Nietzsche's past. There is no such thing as a pretext or a philosophy. Belyjs concern is to integrate different thought systems into his artistic work, to confront them with each other and thus to create a dialogue.